Willingness to compete in dirty competitions - Thomas Buser; Sahar Sangi (Tinbergen Institute, 2025)
Competitive environments often leave room for "dirty" practices such as sabotage, retaliation, or dishonesty. We use an online experiment to document aggregate levels and individual differences in the willingness to engage in dirty competition and in the willingness to enter competitions where the opponent may play dirty. We then use the experimental data to validate a set of survey questions that capture willingness to engage in dirty competition above general willingness to compete. We elicit these questions in a representative survey panel and show that willingness to engage in dirty competition is a strong predictor of holding a management or supervisory position and of working in the private - versus the public - sector, but also of worse self-esteem, worse social relationships, and increased feelings of guilt and shame. Men, younger people, and lower-educated people are on average more willing to engage in dirty competition.
Keywords: C91; J24; 330; preferences; personality; sabotage; career choice